Baicalin Enhanced Oral Bioavailability of Sorafenib in Rats by Inducing Intestine Absorption - Wei, Jingyao; Liu, Ruijuan; Zhang, Jiali; Liu, Shuaibing; Yan, Dan; Wen, Xueqian; Tian, Xin (Frontiers in Pharmacology, 2021)
Background: Sorafenib (SOR) has been used as the first-line therapy for advanced hepatocellular carcinoma (HCC). Baicalin (BG), serves as adjuvant therapy for hepatitis which recognized as the major risk factors for the development of HCC, commonly co-administrated with SOR in clinic. This study was aimed to investigate the effect of single and multiple doses of BG on the pharmacokinetics of SOR in rats and the potential mechanism. Methods: Pharmacokinetic parameters of SOR was determined in rats after administration of SOR (50 mg/kg, i.g.) to rats in the presence and absence of BG (160 mg/kg, i.g.) for single and multiple doses. RLMs which isolated from their livers were analyzed for CYP3A and SOR metabolism activities. HLMs were utilized to evaluate the effects of BG on the metabolism of SOR. The effects of BG on the intestine absorption behaviors of SOR were assessed In Situ Single-Pass rat intestinal perfusion model. Results: Single or multiple doses of BG (160 mg/kg, i.g.) significantly increased the Cmax, AUC0–t and AUC0–∞ of orally administered SOR by 1.68-, 1.73-, 1.70- fold and 1.57-, 1.25-, 1.24- fold in male rats and by 1.85-, 1.68-, 1.68- fold and 2.02-, 1.65-, 1.66- fold in female rats, respectively (P<0.01 or P<0.05). Further study revealed that there were no significant differences of Km, Vmax and CLint of 1-OH MDZ and SOR N-oxyde in RLMs between control and multiple doses of BG treated groups. BG has no obvious inhibitory effects on the metabolism of SOR in HLMs. After combining with BG, the permeability coefficient (Peff) and absorption rate constant (Ka) was significantly increased in comparison to that SOR alone in Situ Single-Pass rat intestinal perfusion model. Conclusion: BG enhanced the oral bioavailability of SOR significantly in rats, which may be mainly attributable to intestine absorption induction. A greater understanding of potential DDIs between BG and SOR in rats may provide basis guidance for rational multidrug therapy in HCC patients. Clinic trails in human and HCC patients need to be further confirmed in the subsequent study.